2014
DOI: 10.1097/rlu.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Gated SPECT Myocardial Perfusion Imaging, Intraventricular Synchronism, and Cardiac Events in Heart Failure

Abstract: A rest gated SPECT is a valid approach to identify HF patients most likely to experience cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Our group conducted a previous study using resting gated SPECT perfusion scintigraphy on dilated cardiomyopathy patients, which also assessed perfusion, function and synchrony, but did not consider the effect of exercise on these variables. [14] It was found that presence of ischemia, SRS and phase SD were the variables that showed greatest association with adverse event occurrence during followup, which supports our current results concerning abnormal resting-phase SD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our group conducted a previous study using resting gated SPECT perfusion scintigraphy on dilated cardiomyopathy patients, which also assessed perfusion, function and synchrony, but did not consider the effect of exercise on these variables. [14] It was found that presence of ischemia, SRS and phase SD were the variables that showed greatest association with adverse event occurrence during followup, which supports our current results concerning abnormal resting-phase SD.…”
Section: Discussionsupporting
confidence: 90%
“…Only 5 patients who had heart events were nonischemic, whereas 39 (89%) were ischemic. [14] The purpose of this study was to assess the value of stress-rest protocol gated SPECT-the information it provides on myocardial perfusion, ventricular function and intraventricular synchronyfor identifying symptomatic HF patients who are likely to develop adverse cardiac events.…”
Section: Introductionmentioning
confidence: 99%
“…Gated-SPECT MPI can help differential diagnosis between ischemic and non-ischemic ventricular dysfunction. As it has already been shown, ischemic etiology generally causes diffuse, severe, and extensive perfusion defects in coronary artery distribution, as well as focal WM abnormalities, whereas those with non-ischemic ventricular dysfunction have either homogeneous tracer uptake or mild to moderate perfusion defects in non-coronary artery distribution, as well as diffuse WM abnormalities [31,32]. This coincides with our results, where mean SRS was signi cantly higher for ischemic patients (14.9±7.1) vs. 9±3.9 (non-ischemic) and 8.7±4.4 (non-compaction CM patients), p<0.0001.…”
Section: Discussionmentioning
confidence: 96%
“…Gated-SPECT MPI contributes to the differentiation between ischemic and non-ischemic ventricular dysfunction. Ischemic dysfunction usually causes diffuse, severe, and extensive perfusion defects and wall motion abnormalities in coronary artery distribution, whereas those with non-ischemic etiology have either homogeneous tracer uptake or mild to moderate perfusion defects in non-coronary artery distribution, as well as diffuse wall motion abnormalities [32,33]. This coincides with our results, where mean SRS was significantly higher for ischemic patients (14.9 ± 7.1) versus 9 ± 3.9 (non-ischemic) and 8.7 ± 4.4 (noncompaction CM patients), p < 0.0001.…”
Section: Discussionmentioning
confidence: 99%